INOVASI PELAYANAN TRANSPORTASI PUBLIK KERETA COMMUTER INDONESIA DI WILAYAH JABODETABEK - Fachrian, Fafa Afief; Ode, Samsul (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2018)
The train is one of public transportation that can be easy for human’s activities, the gevornment as organized of public sercvice needs to give ensure of tools availability and facilities of public transportation that used by society. This research tries to analyze about the quality reached of public transportation service through the approachment of Inovation Public Service theory as one the important of yardstick in public service that be applied based on The Law Number. 25 year 2009 about public service is the law that regulates about a good government principles which is the effectiveness of governments functions. The public service is organized by government or effective corporation that can be supported of the democracy and human’s right, promote economy prosperity, social prosperity, relieve the proverty, increase the environment safety, wise utilization of natural resource, deeepen in trust to government and public administration. In this research, the researcher uses the descriptive qualitative research method, the aggregated data technique through doing observation, interview, and analysis by triangulation resource, then all the research activities is measured by some inovation theories and public service principle. The researcher is able to summarize the KCI Company has gotten public credibility, because it can be proofed through passenger data that rise up drastic as long as in 2017. The inovation of service as content of public service yardstick for measuring the result research by proving that each services of KCI company is gave that be entered in enough good step in practising.